A Modified Fractal Bow Tie Antenna for an RFID Reader - Chaouki Guesmi; Abdelhak Ferchichi; Ali Gharsallah (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In this paper, fractal Bowtie antennas are proposed. To validate our structure and to develop an analytic method to determine the geometry parameters, the Lumped theory is used. The proposed structure is simulated using CST Microwave Studio and then Compared to the electrical Model. The proposed circuit has the same resonant aspect when comparing to the Bowtie antenna with a much reduced simulation time. The Bowtie antenna has a box with a size of   44 *80 *1.5 mm3. This antenna will be designed to an RFID Reader that resonates on 2.45 GHz.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5656